The Ecotoxicity Approach as a Tool for Assessing Vermiremediation Effectiveness in Polychlorobiphenyls, Polychlorodibenzo-p-Dioxins and Furans Contaminated Soils - Remelli, Sara; Celico, Fulvio; Menta, Cristina (Frontiers in Environmental Science, 2022)
Chemical analyses are inadequate for assessing soil biological quality. Instead, the soil living community can be used both for monitoring and restoring soil health. The aim of this research was to verify vermiremediation efficiency in PCDD/F and PCB contaminated soils from Brescia-Caffaro (Italy), using an ecotoxicity approach. To gauge whether Caffaro soil could sustain a living community, a characterization of the arthropod community was conducted. Earthworms’ suitability for soil bioremediation was assessed applying ecotoxicity tests. Five treatments were set up: (i) contaminated soil; (ii) contaminated soil + Eisenia fetida; (iii) contaminated soil + Lepidium sativum; (iv) contaminated soil + E. fetida + L. sativum, (v) uncontaminated soil + E. fetida. The ecotoxicity tests were: L. sativum germination index and root elongation inhibition, and Folsomia candida survival and reproduction, applied on soil and elutriate on: starter soil (T0), after 56 and 112 days (T56 and T112), the last after water percolation. Soil arthropod community was dominated by Hypogastruridae, Oribatida and, to a lesser degree, Formicidae and Coleoptera larvae. Ecotoxicity tests showed that F. candida reproduction and L. sativum root elongation were more adversely affected by pollutants than survival and germination. The higher soil ecotoxicity at T112 than at T56, suggested higher contaminant bioavailability after water addition. F. candida showed more variability between soil and elutriate than L. sativum. Both bioassays suggested earthworm treatment as the most promising. The importance of selecting different organisms in soil ecotoxicity monitoring, and the role of elutriate like a solid phase complement, was highlighted.